HUBUNGAN ANTARA POLA ASUH DEMOKRATIS DENGAN KEMATANGAN EMOSI PADA SISWA SMA NEGERI 9 SAMARINDA. - Purwanti, Ika Dian (MOTIVASI, 2013)
This study aims to determine whether there is a relationship between democratic parenting with emotional maturity level of the students of SMA Negeri 9 Samarinda in terms of the aspects of each democratic parenting variables as the independent variable (X) and emotional maturity as the dependent variable (Y) .The research was conducted in class I and class 2 SMA Negeri 9 Samarinda. Samples totaling 159 students drawn with probability sampling technique. Types of research used in this study is a quantitative correlation. Formula used for the calculation of reliability Cronbach's Alpha. To test the statistical analysis used product moment correlation, with the help of the statistical program SPSS 13.Normality test showed normal results (p> 0.05), namely for emotional maturity and p = 0.704 for democratic parenting p = 0.290. Linearity test results stated linear (p> 0.05), namely p = 0.10 for democratic parenting-emotional maturity. For the analysis of the results of hypothesis testing using product moment correlations with outcome r = 0.043, and p = 0.590. Rules that are used is if p <0.05 then there is a significant relationship anatara two variables. because p = 0.590> 0.05 then it means that the major hypothesis in this study was rejected.